2019
DOI: 10.1001/jamanetworkopen.2019.2906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Hard-to-Treat Childhood and Adolescent Cancers

Abstract: IMPORTANCE Little progress in pediatric cancer treatment has been noted in the past decade, urging the development of novel therapeutic strategies for adolescents and children with hard-totreat cancers. Use of comprehensive molecular profiling in the clinical management of children and adolescents with cancer appears a suitable approach to improve patient care and outcomes, particularly for hard-to-treat cases. OBJECTIVE To assess the feasibility of identifying potentially actionable mutations using nextgenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 41 publications
(86 reference statements)
0
23
0
Order By: Relevance
“…exome sequencing and analyses. Exome sequencing and analyses were performed as previously described 33 ; whole exomes were captured using Agilent's SureSelect XT Clinical Research Exome kit per manufacturer's protocol and librairies were sequenced on Illumina high throughput sequencers (HiSeq 2500 or 4000 in paired-end 2 × 75b.p. or 2 × 100b.p.)…”
Section: Single Cell Rna Sequencing and Analyses Thawed Bmmcs Were Lmentioning
confidence: 99%
“…exome sequencing and analyses. Exome sequencing and analyses were performed as previously described 33 ; whole exomes were captured using Agilent's SureSelect XT Clinical Research Exome kit per manufacturer's protocol and librairies were sequenced on Illumina high throughput sequencers (HiSeq 2500 or 4000 in paired-end 2 × 75b.p. or 2 × 100b.p.)…”
Section: Single Cell Rna Sequencing and Analyses Thawed Bmmcs Were Lmentioning
confidence: 99%
“…The prognosis of HB is associated with several factors, such as initial AFP level, age, co-morbidity and pathological subtype ( 38 ). At present, the research on the genotypes of HB-associated disease is mostly associated with the research of targeted therapy ( 39 , 40 ). In the present study, the CR rate of the gene abnormality group was lower than that of the non-reported disease-associated gene abnormality group.…”
Section: Discussionmentioning
confidence: 99%
“…We will discuss these aspects separately in the next sections. The following precision medicine programs were developed: the United States initiated BASIC3 [40], MSKCC PMTB [41], PIPseq [42,43], Peds-MiOncoSeq [44], ClinOmics [45], UCSF [46], iCAT [47] and pediatric MATCH [48]; Canada initiated PROFYLE [49], TRI-CEPS [50] and KiCS [51]; France initiated MMB [52], MOSCATO-01 [53], ProfiLER [54] and MAPPYACTS [55]; Australia initiated TARGET [56] and the Zero Childhood Cancer Program [38]; Germany initiated the INFORM study [39,57]; the Netherlands initiated the individualized THERapy (iTHER) program [58,59]; the United Kingdom initiated SM-Paeds [60]; Korea initiated SMC [61] and finally the transnationalPacific Pediatric Neurooncology consortium was initiated [62]. An overview of reviewed precision medicine program characteristics is shown in Table 1 and Figure 2.…”
Section: The Development Of Precision Medicine Programs In Pediatric Oncologymentioning
confidence: 99%